The clinical academic workforce in Australia and New Zealand: report on the second binational summit to implement a sustainable training pathway. Issue 4 (April 2017) - Windsor, John; Garrod, Tamsin; Talley, Nicholas J.; Tebbutt, Carmel; Churchill, James; Farmer, Elizabeth; Baur, Louise; Smith, Julian A.
Abstract : There has been a decline in the proportion of clinical academics compared with full‐time clinicians, since 2004. A Working Party was established to help develop and implement a model for the training of clinical academics. After a highly successful first summit in 2014 that summarised the challenges faced by clinical academics in Australia and New Zealand, a second summit was convened late in 2015 to report on progress and to identify key areas for further action. The second summit provided survey results that identified the varied training pathways currently offered to clinical academics and the institutions willing to be involved in developing improved pathways. A literature review also described the contributions that clinical academics make to the health sector and the challenges faced by this workforce sector. Current training pathways created for clinical academics by Australasian institutions were presented as examples of what can be done. The perspectives of government and research organisations presented at the summit helped define how key stakeholders can contribute. Following the summit, there was a strong commitment to continue to work towards developing a sustainable and defined training pathway for clinical academics. The need for a coordinated and integrated approach was highlighted. Some key objectives were agreed upon for the next phase, including identifying and engaging key advocates within government and leading institutions; publishing and profiling the contributions of successful clinical academics to healthcare outcomes; defining the stages of a clinical academic training pathway; and establishing a mentoring programme for training clinical academics.